2012
DOI: 10.1016/j.rppneu.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência do consumo de tabaco em adolescentes escolarizados portugueses por sexo: podemos estar otimistas?

Abstract: The prevalence of smokers among Portuguese school-aged adolescents varies within the several regions of the country, similar to what happens in the adult Portuguese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…4,26 In a recent study, Figueiredo et al 16 observed that the prevalence of smoking in a sample of adolescents aged from 12 to 17 years was 5.7%, considering several Brazilian cities. Their findings were similar to those of the present study and their prevalence can also be considered low.…”
Section: Discussionmentioning
confidence: 99%
“…4,26 In a recent study, Figueiredo et al 16 observed that the prevalence of smoking in a sample of adolescents aged from 12 to 17 years was 5.7%, considering several Brazilian cities. Their findings were similar to those of the present study and their prevalence can also be considered low.…”
Section: Discussionmentioning
confidence: 99%
“…Os alunos mais velhos da amostra revelaram maior prevalência de consumo e experimentação do que os mais novos, tal como no estudo Health Behaviour in School Aged Children (Ferreira & Matos, 2009) e no de Precioso et al (2012). No entanto, a prevalência de consumo regular ao nível dos alunos do 9.º ano (2,8% nos rapazes e 11,1% nas raparigas) e do 10.º ano (15,3% nos rapazes e 12,5% nas raparigas) enquadra-se nos valores obtidos por Precioso et al (2012) para o contexto nacional.…”
Section: Discussionunclassified
“…No entanto, a prevalência de consumo regular ao nível dos alunos do 9.º ano (2,8% nos rapazes e 11,1% nas raparigas) e do 10.º ano (15,3% nos rapazes e 12,5% nas raparigas) enquadra-se nos valores obtidos por Precioso et al (2012) para o contexto nacional. Note-se, porém, se levarmos em conta as percentagens dentro de cada sexo, temos consumos no 9.º ano de 5,6% entre os rapazes e de 22,2% entre as raparigas.…”
Section: Discussionunclassified
See 1 more Smart Citation